Igreja, uma comunidade terapêutica para infância e juventude - Santiago, Rita Cristina Coelho de Almeida (2007)
This work deals with the question: how the Baptist church will develop work with its children and teenagers members, in such a way to answer today's society challenges faced in these age groups? Through this research, a psychological and theological analysis is presented to make possible the therapeutic praxis in church, describing the criteria and biblical examples as well as Sigmund Freud s psychological and psychoanalytical basis. It analyses the Baptist Congregation as a favorable place to promote human essence healing in its completeness. For this reason, it makes use of the research-action methodology. Some children and some young people were interviewed, when they talked about their own lives and what image of God they have. As theoretical references, bibliographies from the authors Erik Erikson, Sigmund Freud, Gary Collins and H. Clinebell were consulted. This work is divided into three chapters. The first one demonstrates the Baptist church s need to promote a therapy for children and youth inserted in a secularized society; some aspects are pointed out from postmodern context, from the psychosocial stages and from the faith stages, as well as the church s challenge to promote abundant life. The second chapter explains the church s mission as a therapeutic community; there is a brief review about the origins of Baptist church in Brazil and a special emphasis in the church s mission. The third chapter seeks to point ways for therapeutic praxis development in the Baptist church. Finally, the fourth and final chapter presents suggestions to manage the problem raised by this research.